2014
DOI: 10.3928/01477447-20141124-50
|View full text |Cite
|
Sign up to set email alerts
|

BMP-7 Versus BMP-2 for the Treatment of Long Bone Nonunion

Abstract: The authors compared the results of treating nonunion with either bone morphogenetic protein (BMP)-7 or BMP-2. Between 2001 and 2009, 214 limb segments were treated for nonunion with either BMP-7 or BMP-2 at the authors' institution. Sixty-three subjects received 76 units of BMP-7. Radiographic healing occurred in 70% of limb segments at an average of 30 weeks after surgery, and 75% of limb segments were weight bearing at an average of 23 weeks after surgery. In 15.8%, persistent nonunion necessitated addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 46 publications
2
31
1
1
Order By: Relevance
“…Only one of these femoral nonunions healed after initial rhBMP-7 application; one healed after additional surgery with iliac crest bone grafting [24]. For the treatment of long bone nonunions, better results regarding the rate of union and the time to union have been reported for rhBMP-2 compared to rhBMP-7 use in a recently published study [25]. …”
Section: Discussionmentioning
confidence: 99%
“…Only one of these femoral nonunions healed after initial rhBMP-7 application; one healed after additional surgery with iliac crest bone grafting [24]. For the treatment of long bone nonunions, better results regarding the rate of union and the time to union have been reported for rhBMP-2 compared to rhBMP-7 use in a recently published study [25]. …”
Section: Discussionmentioning
confidence: 99%
“…In general, while there is a tendency to use rhBMPs for certain indications, there is no consensus about the best BMPs for the regeneration of each specific bone pathology and the only comparison was performed by Conway et al [56] in a retrospective study, with a higher and faster rate of radiographic bone non-union healing with rhBMP-2 compared to rhBMP-7, and no difference in the complication rate between groups. However, the overall lack of well-designed comparative studies prevents determining if both BMPs are equally effective or if they differ in terms of enhancement potential of bone healing in heterogeneous orthopaedic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, this literature research also revealed that most of the clinical findings are based on case reports or case series with small patient populations, characterized by different delivery approaches, anatomical locations, bone pathologies and dosages, which makes it difficult to draw any final conclusion about the real potential of BMPs therapy and the best protocol they can be applied to [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. Therefore, further research in this direction is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Bone nonunion is a serious problem that may occur following bone fractures and segmental defects, resulting in a heavy financial burden for both the patient and for the government due to health care costs and the reduced ability of the patient to work [1,2]. Approximately 5% to 10% of fractures result in bone nonunion.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 5% to 10% of fractures result in bone nonunion. An improved understanding of bone biology could facilitate the treatment of bone nonunion [1]. Upon bone damage, bone mesenchymal stem cells (BMSCs) migrate to the damaged portion of bone and differentiate into osteoblasts, which secrete large amounts of extracellular matrix (ECM) to promote bone fracture healing.…”
Section: Introductionmentioning
confidence: 99%